Working Capital and Debt Policy on Profitability of The Companies - Lihard Stevanus Lumapow; Ramon Arthur Ferry Tumiwa (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2020)
Profitability is a measure of a company's success in making a profit. The objectives of this study are: (1) to test and analyze whether profitability is affected by working capital, and (2) to test and analyze whether profitability is affected by debt policy. This research uses quantitative research methods, using a sample of 12 automotive and components companies listed on the Indonesia Stock Exchange in 2012 to 2017 with a purposive sampling technique. The analysis technique in this study uses panel data with multiple regression. The results obtained indicate that working capital has a negative and not significant effect on profitability, as well as debt policy variables have a negative but not significant effect on profitability.